Meet the jedi high council - Dower, Laura; Miralles, Jose (Scholastic New York, 2000)
This book introduces readers to the members of the Jedi High Council, the governing body of the Jedi Order in the Star Wars universe. It provides insight into the roles and responsibilities of each council member, their unique powers, and how they uphold peace and justice across the galaxy. Readers will learn about iconic Jedi Masters such as Yoda and Mace Windu, their wisdom, combat skills, and connection to the Force. The book delves into the history of the council, their decision-making process, and their influence on galactic events. It's a fascinating guide for Star Wars fans eager to learn more about these legendary characters.